THE RELATIONSHIP BETWEEN LEARNING ACTIVITIES AND LEARNING MEDIA WITH STUDENTS' ECONOMIC LEARNING OUTCOMES - Hersan, Hersan; Ogara, Dwi Okaviani; Jariah, Tesi Komariyatun (International Journal of Ethno-Sciences and Education Research, 2022)
This study aims to determine: (1) the relationship between learning activities and economic learning outcomes for students of X Accounting Class at SMK HMPTI Banjar Agung, (2) the relationship between learning media and economic learning outcomes for students in X Accounting class at SMK HMPTI Banjar Agung, (3) the relationship between between learning activities and learning media with economic learning outcomes for students of class X Accounting at SMK HMPTI Banjar Agung. This research is an ex-post facto research. The population in this study were 102 students of class X SMK HMPTI Banjar Agung. Sampling was done using cluster random sampling technique. The results based on the use of cluster random sampling technique obtained class X Accounting as a sample of 40 students. Data were collected using the methods of observation, interviews, documentation, and questionnaires, while the analysis used Product Moment Correlation. The results show that (1) there is a close relationship between learning activities and economic learning outcomes for students of class X Accounting at SMK HMPTI Banjar Agung, with the calculated value obtained thit = 5.3824 and tdaf = 2.02 the difference is 3.3624, thus thit tdaf, (2) there is a close relationship between learning media and economics learning outcomes for students of class X Accounting at SMK HMPTI Banjar Agung, with the calculated value obtained thit = 4.2015 and tdaf = 2.02 the difference is 2.1815, thus hit tdaf, (3) there is a close relationship between learning activities and learning media with economic learning outcomes for students of class X Accounting at SMK HMPTI Banjar Agung, with the calculated value obtained fhit = 3.4125 and fdaf = 3.26 with a difference of 0.1525 test criteria due to thit fdaf. From these calculations, it can be concluded that there is a close relationship between learning activities and learning media with economic learning outcomes for students of class X Accounting at SMK HMPTI Banjar Agung for the 2017/2018 academic year.